The Effect of Roasting Temperature on Ferulic Acid Levels of Robusta Coffee Bean with Thin Layer Chromatography (TLC)-Densitometry - Sugiyanta Sugiyanta1,2, Harianto Notopuro3 , Jusak Nugraha4 , Soetjipto Soetjipto3 , Retno Handajani (Indian Journal of Forensic Medicine & Toxicology, 2020)
The purpose of this study was to quantitatively analyze ferulic acid levels of Robusta coffee bean extractsfrom two samples from different regions (Argopuro and Kaliwining, Jember District), with differentroasting temperatures (180 °C and 200 °C for 10 minutes) using Thin Layer Chromatography (TLC)-Densitometry method. The analytical method used was the TLC-Densitometry, which utilized methanolsolvent p.a; stationary phase: Merck silica Gel 60 F254 plate; chloroform mobile phase: methanol: formicacid (v/v/v) = (85:15:1) in a saturated chromatographic chamber; the test concentration of 50 ppm and theplates were analyzed with the Densitometry winCATS Camag scanner using a UV-Vis detector at 254 nmwavelength and blue fluorescence at 366 nm wavelength. The results showed that the standard correlationcoefficient (R) of ferulic acid was 0.9947. Quantitative analysis of ferulic acid levels obtained on theaverage results of Argupuro coffee bean extract at roasting temperatures 180 °C and 200 °C amounted to1.935598±0.020671 mg/g and 1.419963±0.051633 mg/g, while Robusta Kaliwining coffee bean extract at180°C and 200°C roasting temperature were 3.18087±0.06738 mg/g and 2.420237±0.1989 mg/g. Statisticalanalysis with One-Way Anova obtained p value <0.005. Least Significant Different Test (LSD) obtainedp value <0.005 in each group. Based on the statistical analysis it was concluded that there was an effectof roasting temperature on ferulic acid levels in Robusta coffee bean extract, with the highest ferulic acidcontent obtained in Robusta Kaliwining coffee bean extract in Jember Regency at roasting temperature of180 °C was 3.180875±0.020671 mg/g.